ASSESSMENT OF GENETIC DIVERSITY IN CASSAVA (MANIHOT ESCULENTA CRANTZ.) GENOTYPES - B. BABU RAO,; P. ASHOK,; G. RAMANANDAM,; K. SASIKALA, (The Bioscan, 2015)
The present investigation was carried out at Department of vegetable Science, HC&RI, Dr.Y.S.R.H.U, Venkataramannagudem during 2012-13. All the 18 cassava genotypes were grouped into five clusters based on D2 values, which exhibited no association between geographical distribution and genetic divergence. The genotypes were mainly grouped due to morphological differences but not due to geographical differences. Among the five clusters, cluster IV was largest with 7 genotypes followed by cluster I with 5 genotypes. The intra cluster distance was maximum for cluster IV (17.2) and minimum for cluster III (0.00). The maximum inter cluster distance was observed between clusters IV and V (62.40) followed by clusters II and V (55.11) indicating that there is presence of wide range of genetic diversity among the cassava genotypes. Such genotypes with wide genetic diversity based on their mean values can be utilized for breeding programmes for genetic improvement in cassava. Four characters viz. tuber dry matter content (64.05%), plant dry matter content (20.26%), height of first branching (9.15%), starch content (5.23%) contributed maximum in manifestation of diversity. Greater diversity was observed between cluster IV and V revealed that the genotypes of these clusters can be used for hybridization program to obtain better transgressive segregants to produce new varieties with desirable traits.